2007
DOI: 10.1590/s0021-75572007000700007
|View full text |Cite
|
Sign up to set email alerts
|

Corticoterapia: minimizando efeitos colaterais

Abstract: Objective: To describe the main undesirable side effects of glucocorticoid therapy, mechanisms of action and the necessary measures to minimize side effects.Sources: Author's experience, supplemented with papers published in MEDLINE. Conclusion:In order to choose the best glucocorticoid schedule it is essential to understand the pharmacological characteristics and the biological action of glucocorticoids, allowing the most adequate indication, glucocorticoid dose, mode of administration and the duration of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 2 publications
0
19
0
6
Order By: Relevance
“…Current standard medications involve combination therapies, including inhaled corticosteroids, β 2-agonists, leukotriene receptor antagonists, and others [26, 27]. However, these therapies produce potential side effects, such as retardation of growth, loss of bone mass, induction of insulin resistance, and suppression of the immune system, and do not consistently ameliorate airway inflammation in many asthmatic individuals [24, 28, 29]. Therefore, there is a need for the development of safe and efficacious treatments [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Current standard medications involve combination therapies, including inhaled corticosteroids, β 2-agonists, leukotriene receptor antagonists, and others [26, 27]. However, these therapies produce potential side effects, such as retardation of growth, loss of bone mass, induction of insulin resistance, and suppression of the immune system, and do not consistently ameliorate airway inflammation in many asthmatic individuals [24, 28, 29]. Therefore, there is a need for the development of safe and efficacious treatments [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that high-dose or long-term use of GCs results in several adverse side effects including osteoporosis 1. Epidemiological studies have demonstrated the high incidence of fractures at the spine (the skeletal site rich in trabecular bone), followed by fractures at the hip (the skeletal site rich in both trabecular and cortical bone) 2.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, pode induzir a morte celular por apoptose. * Dados retirados a partir de Longui (2007), Antunes e Belik (2001) Outro ponto que merece ser destacado, se refere ao emprego da corticoterapia de uso sistêmico em pacientes neonatos e a administração pré-natal e neonatal. Segundo Antunes e Belik (2001), o uso de dexametasona ou betametasona no período pré-natal é indicada somente para acelerar a maturação pulmonar fetal.…”
Section: Tumoresunclassified